Integral representation and relaxation of local functionals on Cheeger–Sobolev spaces. (April 2022) - Anza Hafsa, Omar; Mandallena, Jean-Philippe
Abstract: We prove an integral representation theorem for local functionals with polynomial growth defined on Cheeger–Sobolev spaces. More precisely, we give a version of the well-known Buttazzo–Dal maso's integral representation theorem in the framework of Cheeger–Sobolev spaces. The integral representation theorem is used to prove a relaxation theorem.